2009
DOI: 10.1016/j.ecss.2009.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove expansion and rainfall patterns in Moreton Bay, Southeast Queensland, Australia

Abstract: Changes in rainfall pattern have been suggested as a mechanism for the landward incursion of mangrove into salt marsh. The aim of the research was to assess the relationship between rainfall patterns and the spatial distribution of mangrove forests at study sites in Moreton Bay, southeast Queensland, Australia, over a 32-year period from 1972 to 2004. To identify periods of relatively consistent rainfall patterns points at which rainfall patterns changed (change-points) were identified using the non-parametric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(83 citation statements)
references
References 41 publications
3
80
0
Order By: Relevance
“…The authors also mentioned that salt marsh may not keep pace with sea-level rise, which would result in an increase in the frequency of tidal inundation, which again would give the mangrove propagules an advantage over salt marsh establishment. This is because the expansion of mangroves is mainly dependent on the rate of sea-level rise, sedimentation (Rogers et al 2006) and rainfall (Eslami-Andargoli et al 2009). In Park's (2004) study an 'edge invasion' was noted, where a 5-10 m boundary of mangroves was growing on the edge of the salt marsh area and it was suggested that this boundary was kept 'stable' because healthy and thick salt marsh cover prevented the establishment of mangrove propagules.…”
Section: Discussionmentioning
confidence: 98%
“…The authors also mentioned that salt marsh may not keep pace with sea-level rise, which would result in an increase in the frequency of tidal inundation, which again would give the mangrove propagules an advantage over salt marsh establishment. This is because the expansion of mangroves is mainly dependent on the rate of sea-level rise, sedimentation (Rogers et al 2006) and rainfall (Eslami-Andargoli et al 2009). In Park's (2004) study an 'edge invasion' was noted, where a 5-10 m boundary of mangroves was growing on the edge of the salt marsh area and it was suggested that this boundary was kept 'stable' because healthy and thick salt marsh cover prevented the establishment of mangrove propagules.…”
Section: Discussionmentioning
confidence: 98%
“…The results of earlier research in the study area have indicated that, although rainfall was important for mangrove change, it also controlled the contribution of other factors such as land use and human population (Eslami-Andargoli et al 2009. The earlier study showed that the period from 1972-1990 was significantly wetter than the 1990-2004 period (Eslami-Andargoli et al 2009). There were significant differences in the rate of mangrove spatial change between the two periods.…”
Section: Introductionmentioning
confidence: 84%
“…These may include both natural and anthropogenic factors. Eslami-Andargoli et al 2009;Saintilan et al 2009). Although changes to mangroves have occurred in the past in response to long-term environmental change, these are expected to become more rapid and widespread in coming decades in response to human land use and global climate changes (Lyford et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations